PENGARUH TINGGI BEDENGAN DAN MACAM PUPUK TERHADAP HASIL BAWANG MERAH (Allium cepa L. var Aggregatum) - Prana Sukmanaa, Gema Swara; Susilaningsih, Sri Endah Prasetyowati; Maryani, Yekti (Universitas Sarjanawiyata Tamansiswa, 2017)
Onion varieties are crok kuning, grown by local communities or farmers in Bantul, Yogyakarta. The purpose of this study was to determine the effect of bed height on the growth and yield of onion, determine the effect of organic and inorganic fertilizers the right to obtain a maximum yield of onion. The study was conducted in the hamlet beluran, Sidomoyo, Godean, Sleman, Yogyakarta. Altitude of 114 meters above sea level with the soil type regosol. Implementation of research at the end of April until the end of June 2016. The tools needed in this research is the hoe, rulers, scales, raffia rope, sprayer, and stationery. Materials used are onion seeds, cow manure, chicken manure, NPK 15:15:15 fertilizers, and artificial fertilizers KCl. The method used was a complete randomized block design. The first factor is the kind of bed height (B) consisting of B1 = 50 cm B2 = 40 cm B3 = 60cm, factor two is kind of manure (P) consisting of P1 = Land P2 = Cow 10 ton/hectare P3 = Chicken 10 ton/hectare, third factor is the kind of chemical fertilizer (K) consisting of K1 = NPK 625 kg/hectare K2 = KCl 100 kg/hectare. Parameters observed that the number of leaves, plant height, plant fresh weight, dry weight of the plant, tuber weight each hill, tuber number each panicle, weight of tuber each hectare. The results show each bed height is not significantly different to the onion crop yield. Cow manure in the mix with a mean weight of KCl get the best dry plants. Fertilizer treatment was not significantly different results with soil medium (control)